The Effect of Salt Hydrotherapy on Foot Pain Intensity in Patients with Gout Arthritis in The Working Area of Karanganyar Community Health Center - Aprida Dian Kartikasari; Zulfa Mahdiatur Rasyida (Majalah Kesehatan Indonesia, 2026)
Gout arthritis is an inflammatory joint disease caused by uric acid crystal deposition, leading to pain, particularly in the lower extremities, and potentially interfering with daily activities and reducing patients’ quality of life. The condition highlights the need for safe, affordable, and accessible non-pharmacological therapies to support pain management in community settings. This study aimed to analyze changes in foot pain intensity after salt hydrotherapy among patients with gout arthritis in the working area of Karanganyar Community Health Center. A pre-experimental study with a one-group pretest-posttest design was conducted involving 17 respondents selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale before the intervention and after three intervention sessions within one week. The median pain score decreased from 6.00 (IQR 2; range 4–8) before the intervention to 3.00 (IQR 2; range 2–4) after the intervention. Statistical analysis using the Wilcoxon signed-rank test showed a statistically significant difference (Z = -3.671; p < 0.001), with a large effect size (r = 0.89). These findings indicate that salt hydrotherapy was associated with a reduction in foot pain intensity, with a shift in pain category from moderate to mild in the study sample. However, the findings should be interpreted cautiously because the study involved a small sample and no control group.